Mechanisms for limiting migration flows in the controversy of members of the US Congress (1920–1921) - S. A. Grechishkina (Гуманитарные и юридические исследования)
Introduction. In the first third of the XX century, the United States continued to experience a strain on domestic political life due to the continued volume of external migration. During this period, the concerned politicians and public figures actively developed measures to regulate migration processes. Since any change in the law is being discussed within the walls of the highest legislative body of the country, an insight into the history of the work of the US Congress is an indispensable condition to analyze an important migration problem. Materials and Methods. Reference to the documents of the US Congress, legislative acts, as well as the periodical press made it possible to analyze the process of developing measures to limit the immigration flow to the United States in the period 1920–1921. The principle of objectivity and the comparative historical method used in the work made it possible to trace differences in the positions of government representatives, analyze arguments in favor of adjusting migration legislation or preserving existing measures. Analysis. The study has specified that the process of discussion and decision-making was influenced by the party affiliation of members of the Congress. At first, Republicans and Democrats from southern states supported the restrictive measures under discussion. However, by 1921, against the background of the economic recession, the opinions of Democrats changed in favor of open support for restrictionism or tacit consent. Results. The reason for the changes in the positions of the Democrats was the reassessment of the electorate of the party since the restrictive vector of policy was set in 1917 and the delayed effect of the electoral process was no longer feasible. In addition, the outspoken lobbying by large entrepreneurs of their interests on the migration issue, including through representatives of the Democratic Party, was openly criticized by society. Consequently, to maintain political weight, the party was forced to reconsider its attitude to the migration issue. The main mechanism of restriction was the quantitative indicator stipulating a quota for each country.